Internet of Things Based on Situation-Awareness for Energy Efficiency - Schiefelbein, Un Hee; Soligo, Diovane; Maran, Vinícius; de Oliveira, José Palazzo M.; Lima, João Carlos Damasceno; Machado, Alencar (iSys - Journal of Information Systems, 2019)
The reduction of electric energy consumption is considered as one of the main challenges in diverse sectors of the economy. To residential customers, the management of energy consumption can bring significant costs reduction and decreased environmental impact. This work presents a solution based on the use of situation-awareness applied in IOT that helps the users to reduce the consumption of electric energy through its own residence. The practical results obtained in the application of this proposal in a real-live scenario confirmed the option of collecting information directly of electrical appliances and inform the user of their energy expenditures in real-time, allowing the knowledge and the management of their expenses.